2012
DOI: 10.1128/aem.00424-12
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Bacillus thuringiensis at Different Growth Phases by Using an Automated Online Two-Dimensional Liquid Chromatography-Tandem Mass Spectrometry Strategy

Abstract: The proteome of a new Bacillus thuringiensis subsp. kurstaki strain, 4.0718, from the middle vegetative (T 1 ), early sporulation (T 2 ), and late sporulation (T 3 ) phases was analyzed using an integrated liquid chromatography (LC)-based protein identification system. The system comprised two-dimensional (2D) LC coupled with nanoscale electrospray ionization (ESI) tandem mass spectrometry (MS/MS) on a high-resolution hybrid mass spectrometer with an automated data analysis system. After deletion of redundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
2
23
1
Order By: Relevance
“…11). Observation of proteins predicted to participate in acetoin metabolism (Fig_989, Fig_1512 and Fig_3152) are consistent with their previous observation in stationary-phase (but not exponential-phase) proteomes of B. thuringiensis (55) and may reflect the role of acetoin as a secondary carbon source during stationary phase growth of multiple bacterial types (64). In addition, the MITOT1 proteomes revealed a carbon starvation protein (Fig_2079), the cell division protein, FtsH (Fig_3548) and two cold shock proteins (Fig_446 and Fig_3723) which have also previously been associated with proteomes of stationary phase cultures (65, 66).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…11). Observation of proteins predicted to participate in acetoin metabolism (Fig_989, Fig_1512 and Fig_3152) are consistent with their previous observation in stationary-phase (but not exponential-phase) proteomes of B. thuringiensis (55) and may reflect the role of acetoin as a secondary carbon source during stationary phase growth of multiple bacterial types (64). In addition, the MITOT1 proteomes revealed a carbon starvation protein (Fig_2079), the cell division protein, FtsH (Fig_3548) and two cold shock proteins (Fig_446 and Fig_3723) which have also previously been associated with proteomes of stationary phase cultures (65, 66).…”
Section: Resultssupporting
confidence: 87%
“…6). These protein counts are similar to those recovered from other Bacillus proteomes (within a factor of 2) (54, 55), despite limitations due to low biomass densities obtained from anaerobic cultivation.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The process of sample preparation, extraction and digestion of whole-cell proteins, and 2D nano-LC-MS/MS (ThermoFisher, USA) analysis are using previously described methods [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al reported the expression of other proteins in B . thuringiensis by studying proteomics at different growth phases using liquid chromatography–mass spectrometry/mass spectrometry (LC–MS/MS) and carried out preliminary analysis for the associated proteins [ 15 ]. Traditionally, LC is the most widely used proteomic method for analyzing complex protein mixtures prior to MS analysis [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%